Pulmonary Vasodilator Response of Combined Inhaled Epoprostenol and Inhaled Milrinone in Cardiac Surgical Patients. (19th September 2022) - Elmi-Sarabi, Mahsa; Jarry, Stéphanie; Couture, Etienne J.; Haddad, François; Cogan, Jennifer; Sweatt, Andrew J.; Rousseau-Saine, Nicolas; Beaubien-Souligny, William; Fortier, Annik; Denault, André Y.
Abstract : BACKGROUND: Pulmonary hypertension (PH) and right ventricular (RV) dysfunction are major complications in cardiac surgery. Intraoperative management of patients at high risk of RV failure should aim to reduce RV afterload and optimize RV filling pressures, while avoiding systemic hypotension, to facilitate weaning from cardiopulmonary bypass (CPB). Inhaled epoprostenol and inhaled milrinone (iE&iM) administered in combination before CPB may represent an effective strategy to facilitate separation from CPB and reduce requirements for intravenous inotropes during cardiac surgery. Our primary objective was to report the rate of positive pulmonary vasodilator response to iE&iM and, second, how it relates to perioperative outcomes in cardiac surgery. METHODS: This is a retrospective cohort study of consecutive patients with PH or RV dysfunction undergoing on-pump cardiac surgery at the Montreal Heart Institute from July 2013 to December 2018 (n = 128). iE&iM treatment was administered using an ultrasonic mesh nebulizer before the initiation of CPB. Demographic and baseline clinical data, as well as hemodynamic, intraoperative, and echocardiographic data, were collected using electronic records. An increase of 20% in the mean arterial pressure (MAP) to mean pulmonary artery pressure (MPAP) ratio was used to indicate a positive response to iE&iM. RESULTS: In this cohort, 77.3% of patients were responders to iE&iM treatment. Baseline systolic pulmonary artery pressure (SPAP) (odds ratio [OR], 1.63; 95% confidence interval [CI], 1.24–2.16 per 5 mm Hg; P = .0006) was found to be a predictor of pulmonary vasodilator response, while a European System for Cardiac Operative Risk Evaluation (EuroSCORE II) score >6.5% was a predictor of nonresponse to treatment (≤6.5% vs >6.5% [reference]: OR, 5.19; 95% CI, 1.84–14.66; P = .002). Severity of PH was associated with a positive response to treatment, where a higher proportion of responders had MPAP values >30 mm Hg (42.4% responders vs 24.1% nonresponders; P = .0237) and SPAP values >55 mm Hg (17.2% vs 3.4%; P = .0037). Easier separation from CPB was also associated with response to iE&iM treatment (69.7% vs 58.6%; P = .0181). A higher proportion of nonresponders had a very difficult separation from CPB and required intravenous inotropic drug support compared to responders, for whom easy separation from CPB was more frequent. Use of intravenous inotropes after CPB was lower in responders to treatment (8.1% vs 27.6%; P = .0052). CONCLUSIONS: A positive pulmonary vasodilator response to treatment with a combination of iE&iM before initiation of CPB was observed in 77% of patients. Higher baseline SPAP was an independent predictor of pulmonary vasodilator response, while EuroSCORE II >6.5% was a predictor of nonresponse to treatment.